2023
DOI: 10.1186/s12885-023-10848-9
|View full text |Cite
|
Sign up to set email alerts
|

Identifying important microbial and genomic biomarkers for differentiating right- versus left-sided colorectal cancer using random forest models

Abstract: Background Colorectal cancer (CRC) is a heterogeneous disease, with subtypes that have different clinical behaviours and subsequent prognoses. There is a growing body of evidence suggesting that right-sided colorectal cancer (RCC) and left-sided colorectal cancer (LCC) also differ in treatment success and patient outcomes. Biomarkers that differentiate between RCC and LCC are not well-established. Here, we apply random forest (RF) machine learning methods to identify genomic or microbial biomar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…Specifically, SHAP analysis indicated that PRAC1 and HOXB13 contribute to the predisposition towards left-sided CRC. This observation is consistent with outcomes from other studies, highlighting the role of these biomarkers as being differentially expressed depending on spatial location of the disease [22, 23]. HOXC4 and HOXC6 SHAP directionality deviated from expected values from our previous study: the bimodal feature explanations of these genes indicate the relationship of these genes with outcome may be complex, and that their contribution is context dependent.…”
Section: Case Studysupporting
confidence: 91%
See 4 more Smart Citations
“…Specifically, SHAP analysis indicated that PRAC1 and HOXB13 contribute to the predisposition towards left-sided CRC. This observation is consistent with outcomes from other studies, highlighting the role of these biomarkers as being differentially expressed depending on spatial location of the disease [22, 23]. HOXC4 and HOXC6 SHAP directionality deviated from expected values from our previous study: the bimodal feature explanations of these genes indicate the relationship of these genes with outcome may be complex, and that their contribution is context dependent.…”
Section: Case Studysupporting
confidence: 91%
“…Each feature was assigned a p-value, providing a statistical basis for their inclusion in the downstream analyses (Supplementary Table 4). Notably, the small nuclear protein PRAC1 emerged as the top feature, indicating its potential role in the lateralization of CRC, which is a result consistent with many previous studies [22,23]. HOXB13, and the lncRNA ENSG00000242407 were also identified as important features.…”
Section: Identifying Significantly Important Featuressupporting
confidence: 88%
See 3 more Smart Citations